PERAN PEMBINAAN PEMASARAN DIGITAL DALAM MENDORONG PERTUMBUHAN UMKM DI KOTA BATAM - Yopi, Yopi; Sihombing, Jonmaianto (Jurnal Pengabdian Ibnu Sina, 2026)
This activity is part of a community service program aimed at enhancing the capacity of the Bank Sampah Mandiri MSME in Batam City, particularly in financial reporting and eCommerce-based marketing strategies. The MSME operates in the field of waste management as an effort to reduce environmental impact. However, in practice, the enterprise faces challenges in financial management and effective product marketing. Through this program, a series of training and mentoring sessions were conducted both in-person and online to provide participants with an understanding of how to prepare systematic and structured financial reports. Additionally, the training introduced digital marketing strategies through e-commerce platforms as alternative tools for promotion and sales. The results of the program indicated an improvement in participants' ability to compile financial reports and a greater understanding of the importance of utilizing digital technology to support marketing efforts. The MSME has started implementing e-commerce to expand its market reach and enhance operational efficiency. This program not only had a positive impact on the partnered MSME but also has the potential to serve as a model for other small enterprises facing similar challenges. Furthermore, the activity contributed to strengthening the local community’s capacity in digital technology and entrepreneurship, thereby supporting the development of a sustainable, digitally driven community economy.